Chloroquine improves left ventricle diastolic function in streptozotocin-induced diabetic mice - Yuan X; Xiao YC; Zhang GP; Hou N; Wu XQ; Chen WL; Luo JD; Zhang GS (Dove Medical Press, 2016)
Xun Yuan, Yi-Chuan Xiao, Gui-Ping Zhang, Ning Hou, Xiao-Qian Wu, Wen-Liang Chen, Jian-Dong Luo, Gen-Shui Zhang Department of Pharmacology, Guangzhou Medical University, Guangzhou, People’s Republic of China Abstract: Diabetes is a potent risk factor for heart failure with preserved ejection fraction (HFpEF). Autophagy can be activated under pathological conditions, including diabetic cardiomyopathy. The therapeutic effects of chloroquine (CQ), an autophagy inhibitor, on left ventricle function in streptozotocin (STZ)-induced diabetic mice were investigated. The cardiac function, light chain 3 (LC3)-II/LC3-I ratio, p62, beclin 1, reactive oxygen species, apoptosis, and fibrosis were measured 14 days after CQ (ip 60 mg/kg/d) administration. In STZ-induced mice, cardiac diastolic function was decreased significantly with normal ejection fraction. CQ significantly ameliorated cardiac diastolic function in diabetic mice with HFpEF. In addition, CQ decreased the autophagolysosomes, cardiomyocyte apoptosis, and cardiac fibrosis but increased LC3-II and p62 expressions. These results suggested that CQ improved the cardiac diastolic function by inhibiting autophagy in STZ-induced HFpEF mice. Autophagic inhibitor CQ might be a potential therapeutic agent for HFpEF. Keywords: chloroquine, diastolic function, HFpEF, autophagy, diabetic cardiomyopathy, type 1 diabetes mellitus